Horizontal Gene Transfer in Five Parasite Plant Species in Orobanchaceae. (8th November 2018) - Kado, Tomoyuki; Innan, Hideki
Abstract: We sequenced genomes of five parasite species in family Orobanchaceae to explore the evolutionary role of horizontal gene transfer in plants. Orobanche minor and Aeginetia indica are obligate parasites with no photosynthetic activity, whereas the other three ( Pedicularis keiskei, Phtheirospermum japonicum, and Melampyrum roseum ) are facultative parasites. By using reference genome sequences and/or transcriptomes of 14 species from Fabaceae and Poaceae, their major host families, we detected 106 horizontally transferred genes (HGT genes), only in the genomes of the two obligate parasites (22 and 84 for Oro. minor and Ae. indica, respectively), whereas none in the three facultative parasites. The HGT genes, respectively, account for roughly 0.1% and 0.2% of the coding genes in the two species. We found that almost all HGT genes retained introns at the same locations as their homologs in potential host species, indicating a crucial role of DNA-mediated gene transfer, rather than mRNA mediated retro transfer. Furthermore, some of the HGT genes might have transferred simultaneously because they located very closely in the host reference genome, indicating that the length of transferred DNA could exceed 100 kb. We confirmed that almost all introns are spliced in the current genome of the parasite species, and that about half HGT genes do not have any missense mutations or frameshift-causing indels, suggesting that some HGT genes may be still functional. Evolutionary analyses revealed that the nonsynonymous–synonymous substitution ratio is on average elevated on the lineage leading to HGT genes, due to either relaxation of selection or positive selection.